The classification of snails belonging to the subfamily Triculinae (Hydrobiidae-Prosobranchia) in Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh (Academia Journal of Biology, 2006)
Snails belonging to the subfamily Triculinae (Hydrobiidae), up to now are not studied in Vietnam. Recent time, based on a taxonomical analysis of snail samples collected from some mountainous provinces in Northern Vietnam, nine new species to science of Triculinae (Tricula semilunaris sp. nov., T. ovata sp. nov., Pseudotricula undulata sp. nov., P. flexuosa sp. nov., P. taybacensis sp. nov., P. alba sp. nov., P. minuta sp. nov., P. sinhoensis sp. nov. and P. leae sp. nov.) are described in detail. Some remarks on the classification of snails belonging to Triculinae are also presented in this paper.1. Tricula semilunaris Dang et Ho sp. nov. (fig. 1) Shell small, long-conical in shape. Length 4-6 mm, breadth 1.1 mm. Shell thin with colour changing from glossy white to yellow white. Shell smooth, no rib and ridge. 8 whorls rather flated, increasing regularly in size, body whorl equal 1/4 of the spire length. Apex obtuse, sutures single, shallow. Aperture semi-lunar, lip single, thick. Upper angle located in about middle part of the body whorl. Callus thin and continuous. Umblicus short and clear. Operculum unknown. Holotype: length 6 mm, breadth 1.1 mm. Length of aperture 1.2 mm, breath of aperture 0.9 mm. Type locality: Sinho, Laichau province. Paratype: 7 specimens. Distribution: living in streams in Sinho, Laichau province.2. Tricula ovata Dang et Ho sp. nov. (fig. 2) Shell small, long-conical. Length 4-4.5 mm, breadth 1.5 mm. Shell thick, with colour changing from yellow with brown spots to black brown. Shell smooth, no rib and ridge. 7 whorls, increasing regularly insize. Whorls flated, body whorl equal 1/3 of the spire length. Apex rather obtuse. Suture single and shallow. Aperture somewhat ovate, lip thick and single. Upper angle located in about middle part of the last whorl. Umblicus clear and short. Operculum unknown. Holotype: length 4.5 mm, breadth 1.5 mm. Length of aperture 1.1 mm; breath of aperture 0.8 mm. Type locality: Sinho, Laichau province. Paratype: 16 specimens collected from Sinho, Laichau province. Distribution: living in streams in Sinho, Laichau province. Note: this new species differs from the other species of the Tricula genus known in area [4, 7, 8, 9, 12] in shallow sutures, flat whorls, body whorl somewhat short, aperture rather ovate. This new species also differs from T. semilunaris sp. nov. in the number of whorms which is fewer, in the shell colour and the formation of apature.3. Pseudotricula undulata Dang et Ho sp. nov. (fig. 3) Shell small, broad-pyramidal, length 3.5-4.5 mm, breadth 2 mm. Shell smooth, 6 whorls, body whorl inflated, glossy, equal 1/2 of the spire length. Apex somewhat sharped. Sutures single, shallow. Shell thin with colour changing from soil-yellow to black brown. Aperture single, semilunar, upper angle located in middle part of the body whorl. Lip thick, tortuous and moderately protruded up in middle part. Callus thick and continuous. Umblicus shaped in narrow chink. Operculum unknown. Holotype: length 4.5 mm, breadth 1.2 mm. Length of aperture 1.5 mm, breadth of aperture 1.2 mm. Type locality: Quangson streams in Daitu, Thainguyen province. Paratype: 10 specimens collected from Daitu, Thainguyen province. Distribution: living in streams in Daitu, Thainguyen province. Note: this new species differs from other species of this genus in the semilunar aperture, lip tortuous and moderately protruded up in middle part.4. Pseudotricula flexuosa Dang et Ho sp. nov. (fig. 4) Shell small, broad-pyramidal, length 3 mm, breadth 1.1 mm. Shell thin with colour white or brown yellow. Shell smooth, 5 whorls, flated, body whorl not inflated, less than or equal 1/2 of spire length. Sutures double. Aperture double, operculum semilunar. Lip thin, tortuous and stretched around in triangular-like with angles protruded up to form nodules. Callus thin and continuous. Umblicus shaped in very narrow chink, even not clear. Holotype: length 3 mm, breadth 1.1 mm. Length of aperture 1.2 mm, breadth of aperture 1.1 mm. Type locality: stream in Sinho, Laichau province. Paratype: 16 specimens collected from Sinho, Laichau province. Distribution: living in streams in Sinho, Laichau province. Note: this new species Pseudotricula flexuosa sp. nov. differs from other species of the Pseudotricula genus in area in the aperture double, lip tortuous and stretched around in triangular-like with angles protruded up to form nodules.5. Pseudotricula taybacensis Dang et Ho sp. nov. (fig. 5) Shell small, broad-pyramidal, length about 3 mm, breadth about 1.2 mm. Shell thin with colour changing from white to yellowish. Shell smooth, 5 whorls, body whorl inflated and equal or more than 1/2 of spire length. Apex somewhat obtuse. Suture double. Aperture single, shaped in water-drop, upper angle located in middle part of last whorl. Lip single, thin and moderately protruded up in middle part. Callus thick and continuous. Umblicus shaped in narrow chink. Operculum ovate. Holotype: length 3 mm, breadth 1.2 mm. Length of aperture 1.1 mm, breadth of aperture 0.9 mm. Type locality: stream in Sinho, Laichau province. Paratype: 16 specimens collected from Sinho, Laichau province and Dabac, Hoabinh province. Distribution: living in streams in Sinho, Laichau province and Dabac, Hoabinh province.6. Pseudotricula alba Dang et Ho sp. nov. (fig. 6) Shell small, somewhat broad-conical, length 3.5-4.5 mm, breadth 1.5-1.7 mm. Shell thin with colour glassy white, surface smooth, glossy. 6 whorls, body whorl inflated, equal 1/2 of spire length. Sutures double. Aperture somewhat semilunar, upper angle located in middle part of body whorl. Lip thick. Callus thick and continuous. Umblicus shaped in narrow chink and short. Operculum unknown. Holotype: length 3.5 mm, breadth 1.6 mm. Length of aperture 1.3 mm, breadth of aperture 1 mm. Type locality: stream in Sinho, Laichau province. Paratype: 4 specimens collected from Sinho, Laichau province. Distribution: living in streams in Sinho, Laichau province.7. Pseudotricula minuta Dang et Ho sp. nov. (fig. 7) Shell very small, long-conical, length 2.5-3 mm, breadth about 1 mm. Shell thick with colour changing from black brown to black. 5-6 whorls, body whorl not inflated, less than 1/2 of spire length. Sutures single, apex obtuse and eroded. Aperture single, semilunar, upper angle located in about 1/3 of body whorl. Lip thick, inner nacre white. Callus thick and continuous. Umblicus unclear. Holotype: length 3 mm, breadth 1.1 mm. Length of aperture 1 mm, breadth of aperture 0.8 mm. Type locality: stream in Dabac, Hoabinh province. Paratype: 12 specimens collected from Dabac, Hoabinh province Distribution: living in streams in Dabac, Hoabinh province. Note: this new species Pseudotricula minuta sp. nov. is characterised by shell thick and very small, long-conical, lip thick, upper angle located in about 1/3 of body whorl.8. Pseudotricula sinhoensis Dang et Ho sp. nov. (fig. 8) Shell small, pyramidal, length 3-4.2 mm, breadth 1.5 mm. Shell thick, solid with colour changes from black yellos to black. 5 whorls, body whorl inflated, equal 1/2 of spire length. Sutures single or double. Aperture single, semilunar, upper angle located in near middle part of body whorl and far from shell. Lip double, thick. Callus thick and continuous. Umblicus unclear. Holotype: length 4.2 mm, breadth 1.5 mm. Length of aperture 1.2 mm, breadth of aperture 1 mm. Type locality: stream in Sinho, Laichau province. Paratype: 15 specimens collected from Sinho, Laichau province and Dabac, Hoabinh province. Distribution: living in streams in Sinho, Laichau province and Dabac, Hoabinh province. Note: this new species differs from other species of the Pseudotricula genus in shell thick, solid, shell colour black brown, specially upper angle of apertutre far from shell.9. Pseudotricula leae Dang et Ho sp. nov. (fig. 9) Shell small, pyramidal, length 3.5-4.1 mm, breadth 1.8 mm. Shell thick, solid with colour changes from yellow white to brown yellow or black brown. 5 whorls, body whorl inflated, equal 1/2 of spire length. Sutures single or double. Aperture single, ovate, upper angle located in middle part of body whorl. Lip double, thick. Callus thick and continuous. Umblicus shaped in narrow chink and short. Holotype: length 4.1 mm, breadth 1.8 mm. Length of aperture 1.5 mm, breadth of aperture 1 mm. Type locality: stream in Dabac, Hoabinh province. Paratype: 15 specimens collected from Dabac, Hoabinh province and Sinho, Laichau province. Distribution: living in streams in Dabac, Hoabinh province and Sinho, Laichau province